Nordic Societal Security Convergence and Divergence - Larsson, Sebastian; Rhinard, Mark (Taylor & Francis, 2021)
"This book compares and contrasts publicly espoused security concepts in the Nordic region, and explores the notion of societal security. Outside observers often assume that Nordic countries take similar approaches to the security and safety of their citizens. This book challenges that assumption and traces the evolution of 'societal security', and its broadly equivalent concepts, in Sweden, Norway, Denmark and Finland. The notion of societal security is deconstructed and analysed in terms of its different meanings and implications for each country, through both country- and issue-focused studies. Each chapter traces the evolution of key security concepts and related practices, allowing for a comparison of similarities and differences between these four countries. Using discourses and practices as evidence, this is the first book to explore how different Nordic nations have conceptualised domestic security over time. The findings will be valuable to scholars from across the geographical and theoretical spectrum, while highlighting how Nordic security discourses and practices may deviate from traditional assumptions about Nordic values. This book will be of much interest to students of security studies, Nordic politics and International Relations."